MEDIATION PRINCIPLES IN SOCIAL WORK - Norutė, Rūta; Garšvė, Lina (PROFESSIONAL STUDIES: Theory And Practice, 2022)
Annotation The article presents mediation concept and its expression in social work. Mediation principles applied in social work when solving family social problems have been analysed. Mediation is analysed as a procedure of dispute resolution when one or more mediators help the parties to settle the dispute amicably. The main family mediation principles applied in social work practice while implementing mediation process have been analysed. Key words: mediation, social work, mediator, mediation principles.